2011
DOI: 10.4187/respcare.01164
|View full text |Cite
|
Sign up to set email alerts
|

Time to Desaturation Less Than One Minute Predicts the Need for Long-Term Home Oxygen Therapy

Abstract: BACKGROUND: Exercise desaturation in patients with COPD is a pathophysiological phenomenon that is not wholly understood and whose clinical consequences are still unclear. METHODS: Eighty-three patients with moderate to severe COPD and P aO 2 > 60 mm Hg who desaturated during the 6-min walk test were followed for 5 years. Forty-eight patients had early desaturation (S pO 2 fell below 90% less than one minute after starting the walk test). Spirometry, blood-gas measurements, and 6-min walk tests were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
2
16
1
2
Order By: Relevance
“…Previous studies ( 19 , 20 ) have shown that the time to desaturation during the 6MWT is an indicator of the possibility of desaturation during activities of daily living, culminating in severe hypoxemia and the need for oxygen therapy. Jenkins & Cecins ( 21 ) analyzed the adverse events that occurred during the 6MWT in a group of 572 patients with COPD who completed the 6MWT; 345 (47%) of the patients experienced significant desaturation (a ≥ 4% decrease).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies ( 19 , 20 ) have shown that the time to desaturation during the 6MWT is an indicator of the possibility of desaturation during activities of daily living, culminating in severe hypoxemia and the need for oxygen therapy. Jenkins & Cecins ( 21 ) analyzed the adverse events that occurred during the 6MWT in a group of 572 patients with COPD who completed the 6MWT; 345 (47%) of the patients experienced significant desaturation (a ≥ 4% decrease).…”
Section: Discussionmentioning
confidence: 99%
“…One group of authors ( 20 ) showed that, of 83 patients with COPD who performed the 6MWT, 48 experienced early desaturation (SpO 2 < 90% before the first minute) and that, over a 5-year follow-up period, 65% of those patients developed severe hypoxemia and required home oxygen therapy, compared with 11% of the patients who did not experience early desaturation (p < 0.001). Early desaturation is also associated with desaturation during a 24-h period and during most activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of nadir Sp O 2 may have led to the identification of more patients with exertional desaturation. Previous reports concerning the time to desaturation during the 6MWT found that early desaturators had a higher probability of desaturation while performing daily activities and of developing severe hypoxemia requiring long-term oxygen therapy [32,33]. Thus more detailed analyses of the clinical course of COPD patients with exertional desaturation might be possible using nadir Sp O 2 and time to desaturation during the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…These results are concordant with Troosters et al [32], who found that V o 2 (liters/min) showed a plateau after the 3rd min of the 6MWT. The observed fast decline in Sp o 2 in patients with more severe COPD may be of clinical importance as it predicts the need for chronic domiciliary oxygen therapy [33]. At this point it should be mentioned that continuous pulse oximetry is necessary to accurately describe the dynamic changes in Sp o 2 during the 6MWT.…”
Section: Discussionmentioning
confidence: 99%